Identification of differentially expressed genes in human melanoma cells with acquired resistance to various antineoplastic drugs - Grottke, Claudia; Schadendorf, Dirk (International journal of cancer, 2000)
Malignant melanoma displays strong resistance against various antineoplastic drugs. The mechanisms conferring this intrinsic resistance are unclear. To better understand the molecular events associated with drug resistance in melanoma, a panel of human melanoma cell variants exhibiting low and high levels of resistance to 4 commonly used drugs in melanoma treatment, i.e., vindesine, etoposide, fotemustine and cisplatin, was characterized by differential display reverse transcription-polymerase chain reaction (DDRT-PCR). Of 269 mRNA fragments found to be altered in expression level by DDRT-PCR, a total of 11 cDNA clones was characterized after confirmation of a differential expression pattern by Northern blot analyses. These clones include 3 genes (DSM-1, DSM-3 and DSM-5) of known function, 4 previously sequenced genes (DSM-2, DSM-4, DSM-6 and DSM-7) of uncharacterized function and 4 novel genes (DSM-8-DSM-11) without match in GenBank. All of these genes exhibited altered mRNA expression in high level etoposide-resistant cells, whereby 7 genes (DSM-1-DSM-6 and DSM-8) were found to be decreased in the transcription rate in these etoposide-resistant cells. The mRNA synthesis of the remaining genes (DSM-7 and DSM-9-DSM11) was enhanced in high level etoposide-resistant melanoma cells. The expression of 5 (DSM-5 and DSM-7-DSM-10) of the cloned cDNA encoding mRNAs was modulated in various independently established drug-resistant melanoma cells, indicating to be associated with drug resistance. Further characterization of these genes may yield inside into the biology and development of drug resistance in malignant melanoma.